Experimental and kinetic studies on the intrinsic reactivities of rice husk char. (May 2019) - Gao, Xiaoyan; Zhang, Yaning; Xu, Fei; Yin, Zhaoqin; Wang, Yingying; Bao, Fubing; Li, Bingxi
Abstract: In this study, the intrinsic reactivities of chars prepared from rice husk under fast pyrolysis conditions at 700–900 °C in a micro quartz reactor were characterized. The physicochemical structures of collected chars were investigated through scanning electron microscope, energy dispersive spectrometer, and Raman microscope. The intrinsic reaction rates between the pyrolyzed char and CO2 or O2 were measured by a thermogravimetric analyzer, and the influences of reaction temperature and gas pressure on the intrinsic rates were quantified to obtain the kinetic parameters. It was observed that the destruction and melting of char became serious when the rice husk was pyrolyzed at 900 °C. As the pyrolysis temperature increased from 700 °C to 900 °C, the concentration ratio of O/C and the graphitization degree of char decreased. For the char-CO2 reaction, the intrinsic kinetic constants varied within the ranges of 230.74–235.68 kJ/mol for activation energy, 0.309–0.368 for reaction order, and 6.118 × 10 5 –5.710 × 10 5 1/s·Pa m for pre-exponential factor, respectively. For the char-O2 reaction, the corresponding kinetic parameters were within the ranges of 120.97–124.71 kJ/mol, 1.431–1.981, and 2.591–0.024 1/s·Pa m, respectively. Highlights: Physicochemical properties of rice husk chars prepared at 700–900 °C were obtained. Higher temperature leads to more disordered carbon structure in rice husk char. Intrinsic reaction behaviors of char-CO2 and char-O2 were investigated in a TGA. Intrinsic kinetic parameters were determined for rice husk chars.